Macroeconomics - Williamson, Stephen D. (Pearson Education Limited, 2014)
For undergraduate Macroeconomics courses. A modern approach to macroeconomics. Williamson's Macroeconomics uses a thoroughly modern approach by showing students how to build macro economic models from micro economic principles. This approach helps to make the text consistent with the way macroeconomic research is conducted today